[Al2(OH)8]2– Building Blocks Incorporated in Macromolecular Alumopolysiloxane Rings of the Type [O‐SiPh2‐O‐SiPh2‐O‐Al+]n1. Issue 5 (14th January 2014) - Veith, Michael; Hreleva‐Caparrotti, Hinka; Sahin, Fadime; Huch, Volker
Abstract The molecular alumosiloxanes (O‐SiPh2‐O‐SiPh2‐O)3Al2 and (O‐SiPh2‐O‐SiPh2‐O)4[Al(OH)]4 react either with water in diethyl ether, or with 1, 4‐butane‐diol to form the new macro‐cyclic compounds Al6(OH)8(O‐SiPh2‐O‐SiPh2‐O)4(O‐SiPh2‐O‐SiPh2‐OH)2·6H2O (2) or Al6(OH)8(O‐SiPh2‐O‐SiPh2‐O)4(O‐SiPh2‐O‐SiPh2‐O‐CH2–CH2–CH2–CH2–OH)2 (3). As shown by single crystal structure analyses, both compounds 2 and 3 have a center of symmetry, resemble each other structurally and display in their center an [Al2(OH)8]2– unit, which is coordinated in a similar fashion to a 24‐membered [Al4(O‐SiPh2‐O‐SiPh2‐O)4]2+ cycle branched at two aluminum atoms displaying either two (O‐SiPh2‐O‐SiPh2‐OH) (2) or two (O‐SiPh2‐O‐SiPh2‐O‐CH2–CH2–CH2–CH2–OH) (3) arms. The [Al2(OH)8]2– groups are connected to the cycles through oxygen atoms of their hydroxide groups which link to the aluminum atoms of the ring (of the four aluminum atoms in the ring two have a double contact and two a single). Parallel to this bonding, the aluminum atoms of [Al2(OH)8]2– have either a water molecule in their coordination sphere, which is incorporated in a complex hydrogen bridged network including the silanol function (2), or are bonded to the –CH2‐OH group of the siloxane‐alcohol arm of the cycle (3). The aluminum atoms of the central part are in both compounds in the centers of two distorted edge sharing oxygen octahedra (mean Al–O = 1.881(7) Å (2), 1.893(7) Å (3)), while the other four aluminum atoms display a tetrahedral oxygen environment (Al–O = 1.752(8) Å (2), 1.754(8) Å (3)). Whereas all hydroxy groups of the [Al2(OH)8]2– unit in 2 are engaged in hydrogen bonding including further water molecules which make part of the network, the [Al2(OH)8]2– unit in 3 shows fewer hydrogen bridges. We have here a rare example of the same chemical species in a more hydrophilic and a less hydrophilic surrounding. This allows a detailed study of the impact of secondary hydrogen bonding on the structure.